Adsorption of Ni(II) ions from aqueous solutions using natural Bentonite (Latakia University Journal -Basic Sciences Series, 2019)
In this study, natural Syrian bentonite was used from the Tel Rifaat area in Aleppo governorate as a solid phase for adsorption of nickel (ll) ions from aqueous solutions. The coefficient of the distribution of ions on the surface of bentonite was studied in terms of the time of contact (T), the particle size (Vs), the (pH) value of nickel solution and and the solid phase mass (m). Primary concentration effect of the nickel ions was studied and adsorption model was determined. The adsorption experiment was applied to a real produced water sample obtained from tank 247 of the Syrian Oil Transport Company.It was found that the amount of adsorption increases by increasing the contact time from time (1 min ) until reaching the equilibrium time (60 min ). The value of the adsorption until the contact time (24 hours) stay steady.The experiment showed that the amount of adsorption increases by decreasing the particle size of bentonite from the range (1-2) mm until reaching the highest amount of adsorption using the particle size within the range (100 - 250) µm.then, The amount of adsorption decreases until the particle size < (53) µm.The amount of adsorption of the nickel ( ll ) ions increases with pH increase until the range (5-6). After this range, the process of Ion deposition begins.By increasing the bentonite mass, the total removal ratio increases to amaximum value at (2gr/30ml) and the adsorption amount decreases. it was found that the nickel adsorption on the surface of the bentonite follows the Freundlish model.When the experiment was applied to the real water sample, the ratio of nickel removal using raw bentonite was 91.39 ± 0.23%.